How Hospitals Reengineer Their Discharge Processes to Reduce Readmissions. Issue 2 (March 2016) - Mitchell, Suzanne E.; Martin, Jessica; Holmes, Sally; van Deusen Lukas, Carol; Cancino, Ramon; Paasche-Orlow, Michael; Brach, Cindy; Jack, Brian
Abstract : Background: The Re-Engineered Discharge (RED) program is a hospital-based initiative shown to decrease hospital reutilization. We implemented the RED in 10 hospitals to study the implementation process. Design: We recruited 10 hospitals from different regions of the United States to implement the RED and provided training for participating hospital leaders and implementation staff using the RED Toolkit as the basis of the curriculum followed by monthly telephone-based technical assistance for up to 1 year. Methods: Two team members interviewed key informants from each hospital before RED implementation and then 1 year later. Interview data were analyzed according to common and comparative themes identified across institutions. Readmission outcomes were collected on participating hospitals and compared pre- versus post-RED implementation. Results: Key findings included (1) wide variability in the fidelity of the RED intervention; (2) engaged leadership and multidisciplinary implementation teams were keys to success; (3) common challenges included obtaining timely follow-up appointments, transmitting discharge summaries to outpatient clinicians, and leveraging information technology. Eight out of 10 hospitals reported improvement in 30-day readmission rates after RED implementation. Conclusions: A supportive hospital culture is essential for successful RED implementation. A flexible implementation strategy can be used to implement RED and reduce readmissions.